Emotional Intelligence in Children with Severe Sleep-Related Breathing Disorders - Francesca Felicia Operto; Francesco Precenzano; Ilaria Bitetti; Valentina Lanzara; Maria Lorena Fontana; Grazia Maria Giovanna Pastorino; Marco Carotenuto; Francesco Pisani; Anna Nunzia Polito; Daniela Smirni; Michele Roccella (Behavioural Neurology)
Background. Obstructive sleep apnea syndrome (OSAS) affects up to 4% of a pediatric population, with many comorbidities in the medium-long term. Functional alterations in the prefrontal cortex (PFC) may explain why OSAS impacts aspects such as executive functions, memory, motor control, attention, visual-spatial skills, learning, and mood regulation. Emotional intelligence (EI) is a complex neuropsychological function that could be impaired in many clinical conditions. Purpose. The aim of the study is to evaluate the difference in emotional intelligence skills among children with OSAS and healthy subjects (nOSAS). Methods. 129 children (72 males; mean age 7.64±1.98 years) affected by OSAS were compared to 264 non-OSAS (nOSAS) children (138 males; mean age 7.98±2.13) similar for gender, age, and socioeconomic status. In order to assess the emotional quotient, the Bar-On Emotional Quotient Inventory: Youth Version (EQ-i:YV) was used. Results. The comparison for means and standard deviation between OSAS children and nOSAS children for EQ-i:YV scores showed significant differences for Interpersonal, Adaptability, and Stress Management scales and EQ Total score. Conclusions. Our findings highlighted the role of intermittent hypoxia in the genesis of the effects of sleep-related respiratory disorders, which involves also aspects different from physical impairments.